Implementation of Tatanen Education in Bale Atikan in Establishing the Character of Love for The Country in SMPN 2 Pasawahan Purwakarta District - Rahmatilah, Rima; Baharuddin; Suharyat, Yayat (Proceeding International Conference on Education, 2023)
This study aims to determine the implementation of the Tatanen Education Concept in Bale Atikan and the inhibiting factors in forming the character of loving the motherland at SMPN 2 Pasawahan, Purwakarta Regency. This research is a qualitative descriptive study with data analysis using Miles and Huberman. The study results show that the Tatanen Education Concept in Bale Atikan has the following characteristics: a). The concept of education aims to build character in students by loving the school environment. b). Tatanen Education at Bale Atikan has a special curriculum approved through Regent Regulation No. 69 of 2015, namely Tatanen Education at Bale Atikan c). Tatanen learning at Bale Atikan is integrated with all subjects. In implementing the Tatanen concept at Bale Atikan, competence is required through InHouse Training (IHT) activities held regularly by the education unit and strategies carried out by policymakers to strengthen policies legally in collaboration with other government agencies.